Una experiencia como profesor de ELE en la secundaria eslovena - Rodríguez Díaz del Real, Alejandro (Vestnik za tuje jezike, 2012)
On the basis of a practical experience in teaching Spanish as a foreign language at a Slovenian secondary school, the article offers a personal reflection on the difficulties, challenges and obstacles faced by a native speaker teaching literature and other cultural aspects of the Spanish-speaking world. The initial hypothesis is that these topics are completely undesirable, both for teachers, who are increasingly under working pressure, and publishers whose materials do not respond to the needs of students and are increasingly made on a commercial basis. After the analysis of some specific and general factors, we have reached the conclusion that the classic literature within cultural context is also a completely appropriate tool for educational use in the classroom.
Keywords: tuji jeziki; španščina; Spanish; srednja šola; španska književnost; Spanish literature; kulturne vsebine; Slovenia; Slovenija